1977
DOI: 10.1159/000130756
|View full text |Cite
|
Sign up to set email alerts
|

Origin of triploidy and tetraploidy in man: 11 cases with chromosome markers

Abstract: Sixteen triploid and one tetraploid human abortuses were studied for the origin of polyploidy using a sequential Q- and R-banding technique. Ten triploid abortuses provided informative data: one originated in the maternal first meiotic division; five apparently resulted from dispermy; two derived from an error during either the paternal second meiotic division or the first mitotic division; and the last two were of paternal origin. The results indicate that paternal factors, especially dispermy, are the predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 7 publications
2
42
1
Order By: Relevance
“…A few earlier reports were based on the analysis of cytogenetically distinguishable polymorphisms or restriction polymorphisms (Kajii and Niikawa, 1977;Sheppard et al, 1982;Surti et al, 1986). Kajii and Niikawa (1977) reported a zygotic failure to complete the first division in one case with tetraploidy (92,XXXX). Surti et al (1986) reported two cases with tetraploidy due to trispermy, these two cases are the first two and only reported cases to date with the karyotypes 92,XXXY.…”
Section: Discussionmentioning
confidence: 99%
“…A few earlier reports were based on the analysis of cytogenetically distinguishable polymorphisms or restriction polymorphisms (Kajii and Niikawa, 1977;Sheppard et al, 1982;Surti et al, 1986). Kajii and Niikawa (1977) reported a zygotic failure to complete the first division in one case with tetraploidy (92,XXXX). Surti et al (1986) reported two cases with tetraploidy due to trispermy, these two cases are the first two and only reported cases to date with the karyotypes 92,XXXY.…”
Section: Discussionmentioning
confidence: 99%
“…Such a high level of dispermy is in agreement with previous studies based on cytogenetic polymorphisms. 2,11 To the best of our knowledge this is the first report addressing the mode of formation of diandric cases using molecular analysis. No significant differences in the average maternal ages were detected in our series (cases due to digynic meiosis I errors: 31.8 years; digynic meiosis II errors: 31.5 years; and diandric: 30.5 years).…”
Section: Mode and Time Of Formationmentioning
confidence: 95%
“…[1][2][3] Two distinct phenotypes are known to be associated with triploidy. A minority of foetuses presents with moderate growth retardation, proportionately sized body parts and particularly large placentas with partial hydatidiform mole (type I [4][5][6] ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because the unbalanced translocations were associated with congenital malformations and were inherited from a phenotypically normal balanced translocation carrier, it is likely that the extra copy of the triplicated 9 McFadden et al, 10,11 Baumer et al, 12 Daniel et al 13 and Kajii et al 14 Triploidy, trisomy and choice of active X BR Migeon et al segment was expressed. Direct duplications in males and females were also mapped but were not used for exclusions, as both copies are on the same chromosome and might function as one copy rather than two and might be subject to position effects.…”
Section: Inactivation Studiesmentioning
confidence: 99%